Physiologic performance, training, and its evolution in international- versus national-level triathletes of both sexes: what differences are there? - Arévalo-Chico, H.; Sellés-Pérez, S.; Fernández-Sáez, J.; Cejuela, R. (The Journal of Strength and Conditioning Research, 2025)
Limited data for elite male and female triathletes exist in the academic literature. This comparative study examined the training loads and physiologic performance data, for the general preparatory period(s) within the training years 2021-2024, as a function of both sex and competition level, in 33 top triathletes. Twenty-three male and 10 female international- or national-level elite athletes took part in the study. The individual athlete's training data were collected for an average period of 18 ± 2 weeks, at the outset and end of which cardiorespiratory and lactate testing was performed. The nonparametric Mann-Whitney U test was performed to detect statistical differences. Running speed at maximum oxygen uptake (SVO2max) was the test-related variable that showed the greatest differences with performance tier in male (p = 0.001; effect size [ES]: 2.07) and female athletes (p = 0.031; ES: 1.74). Training volume was higher in the international athletes (p = 0.001; ES: 1.52). Moreover, mean weekly training load was significantly positively correlated with physiologic performance in the running and cycling tests, especially with SVO2max (p = 0.651; p < 0.05). However, the extent of physiologic performance improvements that occurred during this period did not differ statistically between groups in any variable. It is important, therefore, that the professional level of an athlete is considered when the coach(es) decide what is his/her most appropriate, assimilable, training load. Both SVO2max and the ability to assimilate high training loads seem to be important variables to take into account in the triathlon talent detection process.